Use of dual lumen ports for red blood cell exchange: A comparison of adults and children with sickle cell disease. Issue 4 (6th July 2020) - Su, Leon; Nizzi, Frank; Jamshidi, Ramin; Gomez, Esteban; Perumbeti, Ajay; Mirea, Lucia; Shah, Sanjay
Abstract: Purpose: Sickle cell patients receiving chronic RBC exchange require a form of long‐term central venous access if peripheral access is inadequate. In adults, dual lumen (DL) ports have been utilized but associated with greater procedure complications and duration when compared to other forms of access. In the pediatric sickle cell population, the use of DL ports for RBC exchange has not been well described. In this retrospective cohort study, RBC exchange procedures utilizing DL ports in the pediatric vs adult sickle cell population were compared. Methods: Medical records were reviewed for 685 RBC exchange procedures performed on 25 patients (11 pediatric and 14 adult) between November 2014 to November 2018. Patient‐level characteristics and outcomes were compared between pediatric and adult patients using the Fisher‐exact and Wilcoxon‐rank sum test. Linear/logistic regression models examined procedure‐level parameters and port characteristics with adjustment for clustering. Results: Compared to adults, pediatric patients had slower average maximum inlet speed (42 vs 53 mL/min, P  < .01), but shorter procedure time (60 vs 75 minutes, P  < .01) and lower rate of access alarms (1% vs 11%, P  < .01). Overall, 0.29 thrombotic events per 1000 port days and 0.04 infections per 1000 port days were observed. Conclusion: For adult and pediatric sickle cell patients, a DL port provides a viable option for RBC exchange. In comparison to adults, pediatric procedures with a DL port will typically be shorter and with less procedural complications due to smaller blood volumes and lower flow requirements.